2008
DOI: 10.1016/s1808-8694(15)30574-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation by imaging methods of cochlear implant candidates: radiological and surgical correlation

Abstract: The preoperative radiological evaluation by CI was effective in identifying anatomic abnormalities, allowing surgeons to avoid, or at least be aware of, possible complications. This study demonstrated that CT and MRI were superior to CT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…This study demonstrated that CT and MRI were superior to CT alone. 5 A similar experience was observed in our study, where CT and MRI were found superior in decision making Role of High-Resolution Imaging in Cochlear Implant Surgery Tiwari et al…”
Section: Discussionsupporting
confidence: 86%
“…This study demonstrated that CT and MRI were superior to CT alone. 5 A similar experience was observed in our study, where CT and MRI were found superior in decision making Role of High-Resolution Imaging in Cochlear Implant Surgery Tiwari et al…”
Section: Discussionsupporting
confidence: 86%
“…We performed CT and NMR in all the 9 patients and observed enlargement of the vestibular aqueduct in 1 patient and incudomalleolar malformation in another. These imaging findings were not thought to be of relevance for contra-indication of surgery 3 . However, they are important in order that the surgeon has notion of the potential intra-operating problems that can take place.…”
Section: Discussionmentioning
confidence: 90%
“…The patient candidates for the IC undergo an evaluation surgical-daily pay. In this evaluation, the imaging examinations including CT and NMR are carried out with the realization that they are of basic importance while making possible the identification of findings that would counter-indicate the surgery, assiting in the choice of the ear being introduced, assessing appropriately the anatomy of the area to be explored during the surgery and, inside their limitations, allowing a previsualization of areas of potential complications 3 . The conjugated use of the CT and NMR of the result in better agreement of the obtained information and help the surgeon intraoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…who found that the sensitivity of CT was 36.36% and the specificity was 86.36%. [ 25 ] This can be explained by the fact that in imaging the jugular bulb is considered high if it reaches the level of the basal turn of cochlea regardless of whether it is hiding round window niche; however, surgeons are dealing only with the high bulb that may interfere with the accessibility of round window.…”
Section: Discussionmentioning
confidence: 99%